Judging Femicides from a Gender Perspective: Special Reference to the Legal Regime of El Salvador (Global Journal of Human-Social Science, 2024)
This article addresses the legal problem of femicide violence in the context of the legal regime of El Salvador Centro Am rica mainly in the field of procedural law in which women suffer due to the lack of a legal figure or a protocol for action in cases of femicide Which establishes an analysis methodology that incorporates the gender perspective as an interpretive criterion It is a socio-legal investigation with an interdisciplinary approach that links the science of law with gender studies It presents a socio-legal problem about the fundamental rights of women in the course and resolution of judicial processes The author presents a position based on theoretical studies jurisprudence and comparative law on the need to develop criteria for judicial action with a gender perspective aimed at the justice administration sector To support positions in the work the reality of El Salvador is analyzed but experiences from other legal contexts such as Mexico Cuba Chile Argentina Guatemala and Nicaragua are also taken up This study concludes with some criteria of fairness of judgment so that those who administer justice can carry out both the interpretation and application of the law with a gender perspective implementing a method to verify if there was a situation of violence or vulnerability in the victim due to gender issues This is a great challenge since it is up to the judiciary to deploy its entire protective approach to people in vulnerable situations especially those who have historically been discriminated against Women
Keywords: justice of el salvador/gender perspective/ femicides / due process/ discrimination/ violence against women